2011
DOI: 10.1162/jocn.2010.21420
|View full text |Cite
|
Sign up to set email alerts
|

A Neurocomputational Model of Dopamine and Prefrontal–Striatal Interactions during Multicue Category Learning by Parkinson Patients

Abstract: Abstract■ Most existing models of dopamine and learning in Parkinson disease (PD) focus on simulating the role of basal ganglia dopamine in reinforcement learning. Much data argue, however, for a critical role for prefrontal cortex (PFC) dopamine in stimulus selection in attentional learning. Here, we present a new computational model that simulates performance in multicue category learning, such as the "weather prediction" task. The model addresses how PD and dopamine medications affect stimulus selection pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 59 publications
6
66
0
Order By: Relevance
“…Finally, we confirmed that the multicue strategy was the optimal strategy, which supports previous findings on strategy use during probabilistic association learning [41,51]. We also found that those with a low expression of schizotypal personality traits used the more optimal multi-cue strategy which is consistent with displaying a significantly better performance.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, we confirmed that the multicue strategy was the optimal strategy, which supports previous findings on strategy use during probabilistic association learning [41,51]. We also found that those with a low expression of schizotypal personality traits used the more optimal multi-cue strategy which is consistent with displaying a significantly better performance.…”
Section: Discussionsupporting
confidence: 89%
“…For example, prior models do not simulate dissociable effects of different PD medications on brain and cognition [52,67]. Most past models have also ignored any potential function of D 2 receptors in the PFC in working memory [67,68], arguing for a more important role for PFC D 1 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the critic is not informed about the action that the actor selects, but is informed about whether the selected action culminated in a rewarding consequence or not. The temporal difference model is utilized to train the model [52]. …”
Section: Model and Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it has been recognized that cognitive functions are impacted as well [3,4,5,6,7,8,9,10]. Understanding the precise nature of these cognitive symptoms and how they are affected by treatment for PD is of tremendous interest to both basic and clinical research.…”
Section: Introductionmentioning
confidence: 99%